2023
DOI: 10.3390/ijms24065160
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Overall Survival by Thymidine Kinase 1 Combined with Prostate-Specific Antigen in Men with Prostate Cancer

Abstract: Thymidine kinase 1 (TK1) is an intracellular enzyme involved in DNA-precursor synthesis. Increased serum TK1 levels are used as a biomarker in various malignancies. We combined serum TK1 with PSA and evaluated its capacity to predict overall survival (OS) in 175 men with prostate cancer (PCa), detected by screening in 1988–1989 (n = 52) and during follow-up (median 22.6 years) (n = 123). TK1 was measured in frozen serum, age was stratified into four groups, and dates of PCa diagnosis and dates of death were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…TK1 might be secreted from tumor cells that are growing actively. Elevated TK1 levels can be detected in both hematologic malignancies and solid tumors 16 . TK1 has been proved to be a new biomarker in several cancers, including hepatocellular carcinoma 17 , prostate cancer 18 , melanoma 19 , and breast cancer 20 et al In addition, TK1 combined with HE4 and CA125 showed a better diagnostic performance in ovarian cancer 21 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…TK1 might be secreted from tumor cells that are growing actively. Elevated TK1 levels can be detected in both hematologic malignancies and solid tumors 16 . TK1 has been proved to be a new biomarker in several cancers, including hepatocellular carcinoma 17 , prostate cancer 18 , melanoma 19 , and breast cancer 20 et al In addition, TK1 combined with HE4 and CA125 showed a better diagnostic performance in ovarian cancer 21 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…One of the essential enzymes for DNA synthesis in tumor cells is thymidine kinase 1 (TK1), which is strongly associated with cell proliferation and has thus far been crucial in determining the effectiveness of many malignancies. [9][10][11][12] Less research has been done on serum TK1 to determine whether cervical cancer that is intermediate or advanced will return following radiotherapy. To predict the recurrence of cervical cancer after radiotherapy, this study developed an innovative nomogram model based on inflammatory factors, serum TK1, and tumor markers and compared its predictive power to that of the TNM staging system and SCC.…”
mentioning
confidence: 99%